Identification and Validation of Conceptual Framework of a Task-based Curriculum Design - Rahimi Fotowat, Faeqeh; Hojjati, Seyed Abdullah; Imanzadeh, Ali (Iranian Journal of Educational Sociology, 2022)
Purpose: This study aims to identify and analyze the conceptual framework of a task-based curriculum design. The focus is on understanding how this approach integrates active, student-centered learning with the practical application of knowledge, aligning curriculum content with global competencies and career readiness.Methodology: A qualitative research design was employed, utilizing content analysis of elementary school textbooks and semi-structured interviews with curriculum experts and educational theorists. Purposeful sampling was used to select 35 textbooks and relevant experts for the study. Data collection continued until theoretical saturation was achieved, and thematic analysis was conducted to identify key themes and patterns related to task-based curriculum components.Findings: The analysis revealed six main domains within the task-based curriculum framework: curriculum design and development, student-centered learning, active and authentic learning, differentiation and adaptation, social learning and collaboration, and assessment and evaluation. These domains emphasize the importance of aligning curriculum with global standards, fostering learner autonomy, integrating authentic tasks, accommodating diverse learning needs, promoting collaboration, and employing task-based assessment methods. The study highlights the critical role of technology integration and continuous curriculum adaptation in maintaining relevance and effectiveness.Conclusion: The task-based curriculum design offers a comprehensive approach that aligns with the demands of contemporary education. By prioritizing active, student-centered learning and the integration of real-world tasks, this approach enhances student engagement, prepares learners for professional challenges, and supports lifelong learning. However, successful implementation requires careful consideration of cultural and contextual factors, ongoing assessment, and adaptation to technological advancements.